Government Capacity to Guarantee Halal Product from Micro, Small, And Medium Enterprises in Kebumen - Norma Sari (Varia Justicia, 2023)
Halal product guarantee is one of the complex and long issues in Indonesia as it took more than 20 years to establish the regulation. The government must fulfill the consumer need for halal product guarantee by providing a reliable certification system. However, there are still many business actors who have not given priority to the importance of halal certification for their products because they think applying halal certification is complicated. Therefore, this research aims to examine the local government capacity to guarantee halal product from micro, small, and medium enterprises (MSME) in Kebumen. It was empirical normative legal research using qualitative approach. In this research, we used primary data collected through interviews, and secondary data sourced from literature study of primary, secondary, and tertiary legal materials. We analyzed the data using a qualitative descriptive approach. The results suggest that the local government capacity to guarantee halal products in Kebumen is advanced in terms of legal capacity. While in community empowerment and utilizing electronic application in halal product certification are still a challenge.